A feasible and accurate method for calculating the radiative properties of soot particle ensembles in flames. (February 2019) - Wang, Ya-fei; Huang, Qun-xing; Wang, Fei; Chi, Yong; Yan, Jian-hua
Highlights: A new method to calculate radiative properties of soot particle ensembles is proposed. Some findings reduce the difficulty of radiative property calculation dramatically. Impacts of particle structure and incident wavelength should not be ignored. Abstract: The accurate calculation of the radiative properties of soot particle ensembles in flames needs to exactly reconstruct the geometric structures of all soot particles and accurately calculate the radiative properties of all soot particles based on their reconstructed geometric structures. However, the enormous number of soot particles in real ensembles makes it practically impossible to implement this task. To solve this problem, a feasible and accurate method is proposed for calculating their main radiative properties except scattering matrix and depolarization ratio. Experimental and numerical results show that soot particles with the same number of primary particles from the same sampling point can be considered as equivalent soot particles, which have almost the same volume, absorption cross-section, scattering cross-section and scattering asymmetry cross-section. Moreover, the average values of these quantities of equivalent soot particles approximately linearly increase with the number of primary particles. These findings can dramatically reduce the difficulty of reconstruction and calculation. The radiative properties of 37 different morphologies of soot particle ensembles in the visible and near-infrared regions ( λ = 0.40–3.00 µm) are calculated using this method, and it is shown that the increasing of the average diameter of primary particles and the average number of primary particles per soot particle can enhance the absorption coefficient, scattering coefficient, asymmetry factor and single-scattering albedo of soot particle ensembles 0.1–900 times. In addition, these radiative properties are found to decrease by at least 70% with the increasing of λ from 0.40 µm to 3.00 µm.